THE ROLE OF TRANSPARENCY IN PREVENTING ADMINISTRATIVE CORRUPTION IN IRAQ AND EGYPT - Researcher. Mohammed Rafid Raoof Al-Awsi; Assistant Professor Dr. Syed Alireza Tabatabai (Scholar Express Journals, 2022)
Corruption and the absence of transparency and administrative integrity are a multifaceted phenomenon with economic, social and political dimensions. Corruption contradicts and collides with a number of concepts, including administrative transparency: “which means the availability of information related to policies, systems, laws, decisions and regulations for all citizens”; Since it is one of the manifestations of administrative underdevelopment in the Arab world in general, and what is related to transparency, there is a severe lack of statistics and information about the administrative activity of the state, and even if these statistics are found, they are old and inaccurate. With administrative transparency colliding with the socalled job secret, which deters the chances of fighting corruption because there is no real fight against corruption without administrative transparency and accurate data available on a regular, modern and consistent basis
Keywords: transparency; administrative system; administrative corruption; Egyptian law